Determinant factors affecting the research performance of lecturers receiving external funds - Haryanto, Haryanto; Kholis, Nur; Hadi, Samsul; Apino, Ezi; Asriadi AM, Muh.; Trizkyana, Cerry Kartika (REID (Research and Evaluation in Education), 2023)
Quality research can positively impact the development of science and technology and improve the reputation of universities. This study investigates the determinant factors that affect the research performance of lecturers who obtain external funding. The sample was 41 lecturers who obtained external research funds from various institutions (e.g., Directorate of Research, Technology and Community Service, Ministry of Education, Culture, Research and Technology of the Republic of Indonesia; National Research and Innovation Agency of the Republic of Indonesia; and similar institutions) for the last three years (2021 - 2023). Cluster analysis using secondary data (Science and Technology Index or SINTA data) was conducted to determine research performance clusters (high and low). Discriminant analysis was conducted to determine the determinant factors affecting research performance achievement based on the cluster analysis results. The results revealed that internal factors, including mastery of English and interest in the research topics offered, are determinant factors that affect the research performance of lecturers receiving external funding. In external factors, eight determinant factors affect research performance, namely: support for dissemination of research results in journals, support from research assistant staff, satisfaction with awards from the university, satisfaction with awards from outside the university, support for research matching funds from the university, training in writing research proposals, ease of obtaining research permits from agencies outside the university, and adequacy of facilities at the university. Universities need to consider these factors to encourage the improvement of the research performance of lecturers receiving external funding.